Genome-wide association study of migraine implicates a common susceptibility variant on 8q22.1 - Anttila, Verneri (2010)
Migraine is a common episodic neurological disorder, typically presenting with recurrent attacks of severe headache and autonomic dysfunction. Apart from rare monogenic subtypes, no genetic or molecular markers for migraine have been convincingly established. We identified the minor allele of rs1835740 on chromosome 8q22.1 to be associated with migraine (p=5.12 × 10(−9), OR 1.23 [1.150-1.324]) in a genome-wide association study of 2,748 migraineurs from three European headache clinics and 10,747 population-matched controls. The association was replicated in 3,202 cases and 40,062 controls for an overall meta-analysis p-value of 1.60 × 10(−11) (OR 1.18 [1.127 – 1.244]). rs1835740 is located between the astrocyte elevated gene 1 (MTDH/AEG-1) and plasma glutamate carboxypeptidase (PGCP). In an expression quantitative trait study in lymphoblastoid cell lines transcript levels of the MTDH/AEG-1 were found to have a significant correlation to rs1835740. Our data establish rs1835740 as the first genetic risk factor for migraine.